Expression of GPR43 in Brown Adipogenesis Is Enhanced by Rosiglitazone and Controlled by PPARγ/RXR Heterodimerization - Jiamiao Hu; Arong Zhou; Peter C. K. Cheung; Baodong Zheng; Shaoxiao Zeng; Shaoling Lin (PPAR Research)
GPR43, a G-protein coupled receptor recognizing short-chain fatty acids, has been reported to participate in many biological functions of white adipocytes, such as adipogenesis and lipolysis. However, the functional role of GPR43 in brown adipocytes is still not clear. In this study, we investigated the effects of the PPARγ agonist rosiglitazone on GPR43 expression in brown adipogenesis. The results demonstrated that GPR43 was expressed during the late phase of brown adipocyte differentiation, which could be further augmented by adipogenic agent rosiglitazone treatment. The PPARγ/RXR heterodimerization was found to be the key transcription factor for this enhancing effect of rosiglitazone on GPR43 expression. Taken together, these results suggested GPR43 levels might be regulated by PPARγ-activated events during brown adipocytes differentiation and reflect the adipogenesis status of brown adipocytes.